Pendampingan Pembiasaan Salat Duha dalam Meningkatkan Akhlakul Karimah Peserta Didik SDN 2 Sukorejo Ponorogo - Eva Dewi Lestari; Fitri Wahyuni; Moh Masduki (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Community service lecture in assisting the habit of Duha prayer at Sukorejo State Elementary School 2. The purpose of this article is whether Duha prayer is able to form students' good character towards fellow friends, teachers and parents and how Duha prayer plays a role in increasing discipline to make their quality better good. The service method used is in the form of Asset Based Community Development (ABCD). The implementation of assistance in getting used to Duha prayers is carried out by providing material in class, reviewing the material and asking questions and answers, then practicing together at the school mosque and practicing Duha prayers in congregation every day. It is hoped that with this assistance in getting used to Duha prayer, students can improve their morals.